2009
DOI: 10.1108/13552550910995452
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between emotional intelligence and entrepreneurial attitudes and intentions

Abstract: PurposeThis paper aims to propose and empirically test a theoretical model positing relationships among emotional intelligence (EI), creativity, proactivity, and attitudes towards entrepreneurship and entrepreneurial intent.Design/methodology/approachA questionnaire survey was completed by a random sample (n=280) of business, engineering and science students across three Greek universities. Results were based on structural equation modelling analysis.FindingsResults provide strong support for the proposition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
188
0
5

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(218 citation statements)
references
References 64 publications
25
188
0
5
Order By: Relevance
“…This proposition is supported by the study which revealed that creativity and proclivity are positively associated to entrepreneurial intention (Zampetakis et al, 2009). In further argument, Wang et al, (2001) revealed that attitudinal variables have significant impact in building entrepreneurial intention.…”
Section: Literature Reviewsupporting
confidence: 73%
“…This proposition is supported by the study which revealed that creativity and proclivity are positively associated to entrepreneurial intention (Zampetakis et al, 2009). In further argument, Wang et al, (2001) revealed that attitudinal variables have significant impact in building entrepreneurial intention.…”
Section: Literature Reviewsupporting
confidence: 73%
“…Researchers like Gorman et al (Gorman et al 1997), Feldman and Bolino (Feldman and Bolino 2000) and Hamidi et al (Yar Hamidi et al 2008) found that high creativity scores positively affect the intention formation process. Zampetakis et al (Zampetakis et al 2009, Zampetakis 2011 in their research study proved that creativity not only affects the intention process but also d positively associated with the attitude toward choosing entrepreneurship as a career.…”
Section: Creativity (Cr)mentioning
confidence: 99%
“…Hence hypothesis (H4a) rejected. In the previous study of emotional intelligence and entrepreneurial intentions, Zampetakis et al 2009 measured the effect of emotional intelligence on attitude and did not test its effect on any other variable of TPB. In the previous study of Ernst (Ernst 2011), subjective norms showed less to no relationship with the antecedents used in the study.…”
Section: Structural Modelmentioning
confidence: 99%
See 2 more Smart Citations